Auto-Reactive Myocarditis and Necrotizing Coronary Vasculitis After Blunt Chest Trauma. (September 2018) - Frustaci, Andrea; Placanica, Giuseppe; Galea, Nicola; Chimenti, Cristina
Abstract : Supplemental Digital Content is available in the text.